2011
DOI: 10.1159/000331265
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Profiles and Thyroid Hormone Regulation of Brain Transcripts in Frogs: A Species Comparison with Emphasis on <i>Physalaemus</i> <i>pustulosus</i>

Abstract: In amphibians, thyroid hormones (THs) are considered key regulators of brain remodeling during metamorphosis, while sex steroids (estrogens and androgens) control sexual differentiation and gonadal development. However, these two endocrine axes can interact during tadpole brain development. Previously, we demonstrated that THs affect sex steroid-related gene expression in the developing brain of Silurana tropicalis and Rana pipiens; however, the gene expression changes differed between species. We chose to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 107 publications
1
8
0
Order By: Relevance
“…Our results showed that rcTRα expression maintained a high level and changed only moderately in the brain throughout metamorphosis, whereas rcTRβ expression changed markedly around climax . These expression profiles of TRα and TRβ in the brain are similar to variations reported for L. sylvaticus and X. laevis, X. tropicalis, R. pipiens, and P. pustulosus (Duarte-Guterman et al, 2012a). These findings suggest that the expression profiles of TRα and TRβ in developing brains have common characteristics for most species of tailless amphibians (Furlow and Neff, 2006;Hogan et al, 2007;Denver et al, 2009).…”
Section: Analysis Of Rctrα and Rctrβ During Metamorphosissupporting
confidence: 85%
See 3 more Smart Citations
“…Our results showed that rcTRα expression maintained a high level and changed only moderately in the brain throughout metamorphosis, whereas rcTRβ expression changed markedly around climax . These expression profiles of TRα and TRβ in the brain are similar to variations reported for L. sylvaticus and X. laevis, X. tropicalis, R. pipiens, and P. pustulosus (Duarte-Guterman et al, 2012a). These findings suggest that the expression profiles of TRα and TRβ in developing brains have common characteristics for most species of tailless amphibians (Furlow and Neff, 2006;Hogan et al, 2007;Denver et al, 2009).…”
Section: Analysis Of Rctrα and Rctrβ During Metamorphosissupporting
confidence: 85%
“…In the brain of X. laevis tadpoles, TRβ mRNA was detected earliest at Nieuwkoop stage 58 and maximal expression occurred at Nieuwkoop stage 60 (which corresponds to Gosner stage 41; Gosner, 1960), and in the juvenile frog, TRβ levels remained at a late prometamorphic level (Krain and Denver, 2004). Recently researchers compared the developmental profiles between TRα and TRβ in the brain of X. tropicalis, R. pipiens, and Physalaemus pustulosus and concluded that TRα does not significantly change during development but TRβ dramatically increases at climax (Duarte-Guterman et al, 2012a). Our results showed that rcTRα expression maintained a high level and changed only moderately in the brain throughout metamorphosis, whereas rcTRβ expression changed markedly around climax .…”
Section: Analysis Of Rctrα and Rctrβ During Metamorphosismentioning
confidence: 99%
See 2 more Smart Citations
“…In Xenopus tropicalis, ERα and ERß genes are expressed at low level in the brain at larval stage 51 (before gonadal sex differentiation which occur between NF54 and NF59 stages), but become extremely abundant in the larva at stage 60 (metamorphic climax). They remain expressed at relatively high levels after metamorphosis, i.e at juvenile stages [137,139]. The precise distribution of estrogen receptors mRNA or proteins have not been studied during development in amphibian species.…”
Section: 1-estrogen Receptors In the Brain Of Amphibiansmentioning
confidence: 99%